Effects of equity and debt financing on SME performance in Malaysia - Mohd Saad, Rosli; Abdul Ghani, Abdullah; Ahmad, Shuhymee; Syed Salim, Syed Mohd Naim (2014)
This study is to examine and verify the existence of relationship between the source of capital via equity and debt financing, and the performance of small and medium enterprise (hereafter SME) in Malaysia.The study is run based on of postal survey using cluster sampling method. It comprises of 177 samples of Malaysian SMEs involving in manufacturing and agriculture sectors. Subsequently, two research hypotheses are developed and analysed.It is found that equity financing has significant positive relationship on the business performance, while debt financing is insignificant.The study suggests that SMEs in Malaysia to employ equity financing as a source of business capital, for its potential (capability) in affecting the performance of business.